Physical Fitness and Academic Achievement: A Case of Kathmandu Valley - Thapa, Sudip (Nepalese Journal of Economics, 2024)
This study examines the physical fitness and academic achievement: A case of Kathmandu Valley. The dependent variable is academic achievement. The selected independent variables are aerobic fitness level, sedentary behavior, nutrition, sleep patterns and sports participation. The primary source of data is used to assess the opinions of respondents regarding aerobic fitness level, sedentary behavior, nutrition, sleep patterns, and sports participation. The study is based on primary data of 110 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of physical fitness and academic achievement: A case of Kathmandu Valley.The study showed a positive impact of aerobic fitness level on academic achievement. It indicates that increase in aerobic fitness level of student leads to increase in academic achievement. Similarly, the study showed a negative impact of sedentary behavior on academic achievement. It indicates that higher the sedentary behavior, lower would be the academic achievement. Likewise, the study also showed a positive impact of nutrition on academic achievement. It indicates that proper balance diet leads to increase in academic achievement. Further, the study observed a positive impact of sleep patterns on academic achievement. It indicates that consistent sleep schedule leads to increase in academic achievement. In addition, the study observed a positive impact of sports participation on academic achievement. It implies that focusing on physical fitness increase in academic achievement.